Atmospheric H2S: Impact on Plant Functioning - Ausma, Ties; De Kok, Luit J. (Frontiers in Plant Science, 2019)
Hydrogen sulfide (H2S) is an air pollutant present at high levels in various regions. Plants actively take up H2S via the foliage, though the impact of the gas on plant functioning is paradoxical. Whereas elevated H2S levels may be phytotoxic, H2S levels realistic for polluted areas can also significantly contribute to the sulfur requirement of the vegetation. Plants can even grow with H2S as sole sulfur source. There is no relation between the rate of H2S metabolism and the H2S susceptibility of a plant, which suggests that the metabolism of H2S does not contribute to the detoxification of absorbed sulfide. In contrast, there may be a strong relation between the rate of H2S metabolism and the rate of sulfate metabolism: foliar H2S absorbance may downregulate the metabolism of sulfate, taken up by the root. Studies with plants from the Brassica genus clarified the background of this downregulation. Simultaneously, these studies illustrated that H2S fumigation may be a useful tool for obtaining insight in the regulation of sulfur homeostasis and the function of sulfur-containing compounds in plants.